2021
DOI: 10.3389/fpsyt.2021.659508
|View full text |Cite
|
Sign up to set email alerts
|

Gaming Disorder and Well-Being Among Emirati College Women

Abstract: Background: The present study examined Internet Gaming Disorder (IGD) and depressive symptom levels among a predominantly female sample of college students from the United Arab Emirates (UAE).Methods: IGD was assessed among two successive cohorts of students at the beginning of the academic year in 2016 and 2019, respectively. All participants (n = 412) completed the Internet Gaming Disorder Scale – Short-Form (IGDS9-SF) and the WHO-5 Well-being Index (WHO-5), a tool widely used for the screening and assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This study found a positive association between IGD scores, average playtime, number of games played regularly, and average money spent on gaming in line with previous studies ( Hawi et al., 2018 ; Rehbein et al., 2015 ). Although multiple studies have reported a higher prevalence among male participants compared to females ( Elnahas et al., 2018 ; Fam, 2018 ; Hawi et al., 2018 ; King and Delfabbro, 2019 ), another study from the UAE found an increase in the prevalence of IGD among females ( Verlinden et al., 2021 ). However, no such a difference was observed in this study which could be because of the limited sample sizes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study found a positive association between IGD scores, average playtime, number of games played regularly, and average money spent on gaming in line with previous studies ( Hawi et al., 2018 ; Rehbein et al., 2015 ). Although multiple studies have reported a higher prevalence among male participants compared to females ( Elnahas et al., 2018 ; Fam, 2018 ; Hawi et al., 2018 ; King and Delfabbro, 2019 ), another study from the UAE found an increase in the prevalence of IGD among females ( Verlinden et al., 2021 ). However, no such a difference was observed in this study which could be because of the limited sample sizes.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence rate rose to 18.20% with a less stringent cutoff (≥ = 21). Although the rate of IGD increased between 2016 and 2019, the respective increase was not found to be statistically significant ( Verlinden et al., 2021 ). Problematic Internet use/computer gaming has been reported among 10% of college students in the US, and is significantly correlated with mental health symptomatology ( Stevens et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study among 370 female university students in Al-Jouf, Saudi Arabia, found that approximately half had moderate to severe internet addiction [34]. A study among predominantly female college students in UAE found an increase in the prevalence of IGD across two-time points, and although this trend was observed among male participants as well, it was more pronounced among female students [35].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate increased to 18.20% when the cut-off was loosened from 14 to 21. According to statistics, the increase in IGD cases from 2016 to 2019 was non-significant (Verlinden et al, 2021). There is a substantial association between internet/computer gaming difficulties and mental health symptomatology (Stevens et al, 2020), and 10% of American college students have reported having problems in this area.…”
Section: Review Of Literaturementioning
confidence: 99%